THEORETICAL ASSESSMENT OF A STIRLING ENGINE 'AMAZON' BY USING PROSA AND MATHCAD - Paula, R. B.; Gonçalves, J. L.; Cobas, V. R. M.; Lora, E. E. S. (Revista de Engenharia Térmica, 2011)
This study describes how to build a prototype Stirling engine named Amazon, focusing on how to apply it to generate electric power in remote areas, with an expected power of 8 kW. Such engine was assessed theoretically by using two different computer software, i.e. PROSA and 'a model to simulate Stirling engines by the theory of Schmidt', which was formulated in Mathcad. The results from Mathcad software were on average 6.8% higher than the results from PROSA software. Such fact occurs since Mathcad does not consider the losses in a real system. Hence, the PROSA is generally more accurate in its results. Modeling performed in Mathcad presents higher values for partial loads and similar values for the project operating point.